Effects of meteorological and agricultural droughts on crop production in Arsi Zone Ethiopia - Tullu, Gezahegn Mergia; Guta, Mekuanint Tariku (Journal of Agriculture and Natural Resources, 2023)
Natural disasters, known as droughts, are mostly brought on by a prolonged decrease in precipitation levels. In the Arsi zone, there is an undiscovered study gap regarding the transmission of drought impacts and factors. The primary goal is to assess how crop output is affected by weather patterns and agricultural droughts while also offering direction for the research area. The Ethiopian Meteorology Institute provided meteorological data, and CHG-UCSB provided CHIRPS data for the years 1991 through 2020. Data on runoff and soil moisture were sourced from USGS FEWS NET between 1991 and 2020, while information on cereal crops was sourced from the Ethiopian Statistical Service between 1995 and 2020. The analysis tools that were employed were ANN, Python, and DrinC. The study’s findings demonstrated the spatiotemporal droughts that stretched across time scales from SPI3 and RDI3 to SPI12 and RDI12. Drought indices showed a range of drought events over short to long time scales, including meteorological, agricultural, and hydrological droughts that were mild, moderate, severe, and intense. The Standardized Precipitation Index (SPI) and the Reconnaissance Drought Index (RDI) showed a significant and increasing propensity to correlate throughout both short and long time periods, but the severity of the droughts differed. With magnitudes of 0.83 across time scales, the maize and barley yield drought correlation was found to be highly correlated. In terms of time scales, the barley and wheat yield drought correlation value was 0.95, while the maize and wheat yield drought correlation was 0.77. Meteorological droughts lead to agricultural droughts, which significantly reduce crop yields in the study area. The degree of the spatiotemporal drought has an impact on the output of wheat, barley, and maize crops throughout time. The results of this work can help improve monitoring and mitigation of droughts, especially for future drought data, and can improve our understanding of the mechanisms causing zonal droughts. This allows us to plan and manage our water resources, soil conservation, and drought-tolerant crop choices in the research region in a more sustainable manner.